1997
DOI: 10.1680/macr.1997.49.179.99
|View full text |Cite
|
Sign up to set email alerts
|

Bond and splitting in bar pull-out: behavioural laws and concrete cover role

Abstract: Concrete splitting originating at the interface of longitudinal rebars is a tricky aspect of R/C structures, since the ensuing loss of bond may cause the premature activation of one of the major failure mechanisms. Consequently, the study of bond after concrete splitting, leading to the formulation of suitable behavioural laws, is still needed, and constitutes the objective of this paper, in order to quantify the loss of bond efficiency in terms of peak strength, initial stiffness, friction and bond-confinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 0 publications
2
37
0
10
Order By: Relevance
“…As pointed out in studies dealing with normal concrete, for low and medium levels of confinement (σl,cc/fc<0.25 [20] or σl,cc/fc<0.30 [39]), the relationship between τb,max/σl,cc and σl,cc/fc follows a linear trend [29]. On the other hand, for high confinement levels, above the previously mentioned limits, the confinement has minimal impact on τ b,max .…”
Section: Bond Strength (τ Bmax ) Vs Lateral Confinement (σ Lcc )mentioning
confidence: 76%
See 2 more Smart Citations
“…As pointed out in studies dealing with normal concrete, for low and medium levels of confinement (σl,cc/fc<0.25 [20] or σl,cc/fc<0.30 [39]), the relationship between τb,max/σl,cc and σl,cc/fc follows a linear trend [29]. On the other hand, for high confinement levels, above the previously mentioned limits, the confinement has minimal impact on τ b,max .…”
Section: Bond Strength (τ Bmax ) Vs Lateral Confinement (σ Lcc )mentioning
confidence: 76%
“…R00) have limited resistance to fracture with limited fracture energy. Consequently, as splitting cracks occur, they are typically uncontrolled [29]. For intermediate level of confinement (CL), R00 and R20 were governed by splitting; R40 had mixed response, whilst in the R60 samples, the rebar pulled out.…”
Section: Bond Slip (τ-S) Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the bursting forces on the surrounding concrete as a result of the wedge action of the ribs Jones, 1995a, 1995b), it has been observed that splitting cracks may develop longitudinally along the bar (Gambarova and Rosati, 1997;Giuriani et al, 1991;Tepfers, 1973). Splitting cracks impair bond mechanical behaviour and make the bond very sensitive to confinement Tepfers, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de fallo es frágil y puede ser originado por ejemplo por un cambio de volumen de una barra debido a corrosión. Sin embargo, conociendo la relación tensión de adherencia local deslizamiento y las condiciones de confinamiento es posible comprobar aunque el recubrimiento se encuentre fisurado si las condiciones del anclaje son o no fiables desde el punto de vista de la seguridad (8).…”
Section: Resultados Obtenidosunclassified